1981
DOI: 10.1182/blood.v57.1.83.83
|View full text |Cite
|
Sign up to set email alerts
|

The kidneys in paroxysmal nocturnal hemoglobinuria

Abstract: Long-term study of 21 PNH patients revealed an unexpectedly high incidence of functional and anatomic renal abnormalities. Most patients demonstrated varying degrees of hematuria and proteinuria distinct from hemoglobinuria. Evaluation of renal function revealed hyposthenuria, abnormal tubular function, and declining creatinine clearance. Radiologically these patients had enlarged kidneys, cortical infarcts, cortical thinning, and papillary necrosis which were confirmed by autopsy studies. Hypertension develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

1985
1985
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(37 citation statements)
references
References 13 publications
0
33
0
4
Order By: Relevance
“…Intravascular haemolysis is associated with many common signs and symptoms in PNH and other haemolytic syndromes including thrombosis, fatigue, impaired quality of life, haemoglobinuria, dyspnoea, dysphagia, abdominal pain, anaemia, and erectile dysfunction (Hillmen et al, 2004Hill et al, 2005c;Rother et al, 2005;Schubert et al, 2008). These signs and symptoms in PNH, and in patients with other haemolytic syndromes, are tied to catastrophic outcomes, including acute renal failure, chronic kidney disease, stroke/ transient ischaemic attack, ischaemic bowel, hepatic failure, and deep vein thrombosis (Clark et al, 1981;Vellenga et al, 1982;Doukas et al, 1984;Hillmen et al, 1995Hillmen et al, , 2007 Adams Hill et al, 2005a,c). Many of these symptoms have been under-recognised as significant contributors to morbidity and mortality in patients with PNH and other haemolytic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular haemolysis is associated with many common signs and symptoms in PNH and other haemolytic syndromes including thrombosis, fatigue, impaired quality of life, haemoglobinuria, dyspnoea, dysphagia, abdominal pain, anaemia, and erectile dysfunction (Hillmen et al, 2004Hill et al, 2005c;Rother et al, 2005;Schubert et al, 2008). These signs and symptoms in PNH, and in patients with other haemolytic syndromes, are tied to catastrophic outcomes, including acute renal failure, chronic kidney disease, stroke/ transient ischaemic attack, ischaemic bowel, hepatic failure, and deep vein thrombosis (Clark et al, 1981;Vellenga et al, 1982;Doukas et al, 1984;Hillmen et al, 1995Hillmen et al, , 2007 Adams Hill et al, 2005a,c). Many of these symptoms have been under-recognised as significant contributors to morbidity and mortality in patients with PNH and other haemolytic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that some measure of renal failure is not uncommon in PNH, fortunately this is mostly of low grade (Clark et al, 1981) and not rate-limiting for the production of EPO. Indeed, in PNH the endogenous EPO levels tend to be very high (higher than in other chronic anaemias: (McMullin et al, 1996): thus, in general there is no clear rationale for the use of EPO in PNH.…”
Section: The Use Of Erythropoietin (Epo)mentioning
confidence: 97%
“…Compared with the general population, patients with PNH have a 62-fold higher risk of a TE (McKeage, 2011) and a six-fold greater risk of chronic kidney disease (CKD) . TEs have been reported to account for up to 67% of PNH-related deaths (Hillmen et al, 2007), while CKD has been reported to account for 8-18% of disease-related mortality (Clark et al, 1981;Nishimura et al, 2004).…”
mentioning
confidence: 99%